[Santa Maria de Ovila Monastery - Vault Bosses] - Hirsch and Kaye::::::::: (1941)
Text on back of photo: "Vault Bosses. S. M. de Ovila. Bosses of vaulting. Lower, center of . . . Boveda. Above a secondary boss, note oblique ... right angle to floor of church."